Procedures of Translation Applied in Translating English Adverbials of Manner into Indonesian in Against All Odds - I Gusti Ayu Agung Sintha Satwika (The Doctoral Studies Program of Linguistics of Udayana University, 2023)
This study aimed to analyze the procedures involved in translatingEnglish adverbials of manner into Indonesian. The data were takenfrom a bilingual biography entitled